Some aspects of the ecology of bushbuck (Tragelaphus scriptus Pallas 1776) in the southern Cape - Odendaal, Pieter Benjamin (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc (Forestry))--Stellenbosch University, 1977.